Theorie und Kritik: Dialoge zwischen differenten Denkstilen und Disziplinen - Gasteiger, Ludwig; Grimm, Marc; Umrath, Barbara (transcript, 2015)
The contributions to this volume investigate the development of theories, the relationship between research programs, and their concept of critical science.